Case Report: Morphological Characterization and Long-Term Observation of Bilateral Sequential Internal Mammary Artery Aneurysms in a Patient With Confirmed FBN1 Mutation - Stengl, Roland; Ágg, Bence; Szilveszter, Bálint; Benke, Kálmán; Daradics, Noémi; Ruskó, Bernadett; Vattay, Borbála; Merkely, Béla; Pólos, Miklós; Szabolcs, Zoltán (Frontiers in Cardiovascular Medicine, 2021)
Marfan syndrome (MFS) is a genetically determined connective tissue disorder that leads to ocular, skeletal and severe cardiovascular involvement. High mortality of MFS is associated with aortic dissection and aneurysm characteristic to the syndrome. In MFS only a few cases of peripheral arterial involvement have been reported so far, mostly without a genetically confirmed diagnosis. We report a 41-year-old MFS patient with a saccular pearl-string-like aneurysm on the right internal mammary artery (RIMA) and a single aneurysm on the left internal mammary artery (LIMA). To our knowledge this is the first reported case on internal mammary artery aneurysms with this special morphology and with follow-up and blood pressure control as primary therapeutic approach in a patient with genetically confirmed MFS. The aneurysms with the above described morphology first appeared as small aneurysms on a CT scan 6 years after a cardiac operation. Due to the lack of guidelines, based on the asymptomatic state of the patient, the increased tortuosity of the affected vessels and the history of prior cardiac surgery, we decided to closely monitor these aneurysms with blood pressure control and without carrying out any interventions. On the CT scans done 3, 11, 12, 17 and 32 months after identifying the aneurysms, no progression of these structures was detected. Our findings confirm the possibility of the occurrence of internal mammary artery aneurysms in patients with FBN1 mutation and we believe that monitoring these aneurysms with blood pressure management can be a suitable option in selected cases.